On the generic placement and taxonomic status of some Miltochrista taxa described by Franz Daniel (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V. (Zootaxa, 2016)
Three Miltochrista Hübner, [1819] taxa described by Daniel, Miltochrista tibeta Daniel, 1951, M. tibeta clara Daniel, 1951 and M. gilva Daniel, 1951 are transferred to the genus Lyclene Moore, [1860]. M. tibeta clara is upgraded to the species level. Adults, male and female genitalia are illustrated.